Prioritization and selection of high fuelwood producing plant species at Boset District, Central Ethiopia: an ethnobotanical approach - Tinsae Bahru; Berhane Kidane; Amsalu Tolessa (BMC, 2021)
Abstract Background In Ethiopia, about 92.3% of all the fuelwood (firewood and/or charcoal) is consumed for cooking, heating and lighting purposes by domestic households and the demand is growing from 10 to 14%. However, there are little/no practical experiences or documented indigenous knowledge on how traditional people identify and select high fuelwood producing plant species with short rotation periods at Boset District. Therefore, the present study was aimed at: (1) selecting and documenting high fuelwood producing plant species at Boset District; (2) identifying major predictor variables that influence the prioritization and selection of species; and (3) develop a Generalized Linear Model (GLM) to predict the selection of species. Methods A total of 96 informants comprising 59 men and 37 women between the ages of 18 and 81 were sampled. Data were collected using structured interviews, guided field walk, discussions and field observations. Results Collected data indicated that 88.5% of the informants involved in firewood collection, while 90% practiced charcoal making. A total of 1533.60 Birr per household on average was earned annually from this activity. A total of 25 fuelwood producing plant species were identified and documented at Boset District. Of these, Acacia senegal, Acacia tortilis and Acacia robusta were the three best prioritized and selected indigenous high fuelwood producing species. Prosopis juliflora, Parthenium hysterophorus, Azadirachta indica, Calotropis procera, Cryptostegia grandiflora, Lantana camara and Senna occidentalis further grouped under introduced fuelwood species. Prediction of GLM assured sampled Kebeles and source of income generated from fuelwood species positively and significantly (p < 0.001) related to selection of species. Higher efficiency to provide energy and heat; little or no smoke or soot; easier to cut and split the wood and easier availability were some of the main selection criteria. Conclusions This study provides valuable information in selecting and documenting of high fuelwood producing plant species for proper management and sustainable use at Boset District. The three most selected species (A. senegal, A. tortilis and A. robusta) should be further evaluated at laboratory to determine their calorific value and combustion characteristics.